Porcine Reproductive and Respiratory Syndrome Virus Infection Induces Stress Granule Formation Depending on Protein Kinase R-like Endoplasmic Reticulum Kinase (PERK) in MARC-145 Cells - Zhou, Yanrong; Fang, Liurong; Wang, Dang; Cai, Kaimei; Chen, Huanchun; Xiao, Shaobo (Frontiers in Cellular and Infection Microbiology, 2017)
Stress granules (SGs) are sites of mRNA storage that are formed in response to various conditions of stress, including viral infections. Porcine reproductive and respiratory syndrome virus (PRRSV) is an Arterivirus that has been devastating the swine industry worldwide since the late 1980s. In this study, we found that infection of PRRSV strain WUH3 (genotype 2 PRRSV) induced stable formation of robust SGs in MARC-145 cells, as demonstrated by the recruitment of marker proteins of SGs, including TIA1, G3BP1 and eIF3η. Treatment with specific inhibitors or siRNAs against the stress kinases that are involved in SG formation revealed that PRRSV induced SG formation through a PERK (protein kinase R–like endoplasmic reticulum kinase)-dependent mechanism. Impairment of SG assembly by concomitant knockdown of the SG marker proteins (TIA1, G3BP1, TIAR) did not affect PRRSV growth, while significantly enhanced PRRSV-induced NF-κB subunit p65 phosphorylation and inflammatory cytokine production. Taken together, our results demonstrate that PRRSV induces SG formation via a PERK-dependent pathway and that SGs are involved in the signaling pathway of the PRRSV-induced inflammatory response in MARC-145 cells.